Assessing the Place of Christo-Peace in Transforming the Life of Nigerian Christians - Kelechi Johnmary Ani (E-Journal of Religious and Theological Studies)
The quest for peace by men has remained a major existential need of man. People go to different places including the church in the search for peace. This study focuses on Christo-peace. Christo-peace is a form of peace that emanates from the communion of man with Christ as well as a strong belief in the teachings of Christ as well as the church. The study is a qualitative research that was developed from the random selection of scriptural quotations from biblical texts. It revealed that Christo-peace is gotten through prayers and ecclesia teachings of the church. It also found that this form of peace has a strong socio-psychological and spiritual impact on the lives of men. The study concluded that Christo-peace as found in the scripture has direct implications on the physical and mental peace of the Nigerian Christians. It recommends the advancement of peace-based preaching, increased prayers for the advancement of prophetic gifts that are needed for Christian understanding of time and the management of the culture of corruption in the Nigerian Christian churches as paths to Christo-peace by Christians, bearing in mind that there are multiple crises undermining the reality of peace on earth.